ChemInform Abstract: Enantioselective Synthesis of α‐Silylamines by Meerwein—Ponndorf—Verley‐Type Reduction of α‐Silylimines by a Chiral Lithium Amide. Issue 45 (23rd October 2014) - Kondo, Yasuhiro; Sasaki, Michiko; Kawahata, Masatoshi; Yamaguchi, Kentaro; Takeda, Kei
Abstract A new and efficient high enantioselective method for the synthesis of a wide variety of α‐silylimines is developed.